An Analysis of Gerund and To Infinitive in Argumentative Essays - Grace Mekaria Unggul; Ingatan Gulö (Universitas Teknokrat Indonesia, 2017)
This article is about gerund and to infinitive usages made by students in their argumentative essays. The research identified grammatical problems occurred in argumentative essays. The theories of Dulay about errors and Harmer about grammar were used. The writers used taxonomies in classifying errors into four types which are omission, addition, misformation and misordering. The method used was library research. In collecting the data, the researchers used students’ papers taken from two classes of a university. The writers concluded that the most common problem in using gerund and to infinitive is misformation. Students found it difficult to use gerunds and to infinitives. It also showed that practice is needed to solve the grammatical problems faced by the students.